A STUDY ON THE ASSERTIVENESS LEVEL OF PHYSICAL EDUCATION AND SPORTS COLLEGE STUDENTS - Erdogan B.S; Erbasi F.Y; Aldemir G.Y; Eraslan M.; Kaya E.; Şahan, H; Yıldız, M (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2015)
The purpose of this study is to examine some of the variables in the level of students' boldness who study at Physical education and sports colleges and to compare the findings with the other studies in the literature. The Research Group contains 92 male and 64 female (/age = 21,612 + 1,921), in total 156 students from Selcuk University physical education and sports college. In order to reach the purpose of the study "Rathus Assertiveness Schedule" has been used as the methodology which is developed by Rathus [12,13], and adopted to Turkish by Voltan [18]. For the interpretation of the data, the Kolmogorov-Smirnov test, one way anova test have been applied and to determine the difference between the groups Turkey test has been applied too. The significance was P <0.05. According to the level of sports; the difference between the average levels of scores of the assertiveness is meaningful [t value = 4,327 P = 0,000 < 0.05]. Looking at average values; average levels of the assertiveness of students doing some sports is ( =86,5614), average levels of the assertiveness of students doing some sports is ( =80,7857). As a result of this study; According to the level of sports observations, the difference between the average levels of scores of the assertiveness is meaningful [t value = 4,327 P = 0,000 < 0.05]. Looking at average values we see that students, who engaged in sports, has been obtained more level of average score of assertiveness than students engaged in no sports. From the point of assertiveness, participation in sport from the perspective of individuals there is a difference in favor of those engaged in sports.